(untitled) (Al-Academy, 2023)
This research deals with one scene from the movie Romeo and Juliet, which is the balcony scene, due to the importance of this scene in the formation of the construction of the subsequent events of the movie. The first chapter contained the methodological framework of the research, where the research problem was identified in how Zeffirelli dealt with the balcony scene in the play Romeo and Juliet and enriched it in the cinematic language with a comparison with the original text of the scene. In the balcony scene with comparative parts between the film and the text and the limits of the research that was limited to the film Zeffirelli and the translated text by Munis Taha Hussein. The second chapter contained the theoretical framework and previous studies, where the theoretical framework included three sections, the first on Shakespeare and the Romantic Theatre, the second on Romeo and Juliet and the construction of the romantic play, and the third, Romeo and Juliet in the cinema. The third chapter included the research procedures, where the researcher used the descriptive and comparative approaches and the research tool extracted from the theoretical framework and previous studies. The fourth chapter contains the results, their discussion, and the analysis of the research sample, the indicators that the researcher reached. The fifth chapter included a summary of results, conclusions, suggestions, sources and supplements